2000
DOI: 10.4049/jimmunol.165.2.680
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the B Cell Receptor, CD86 (B7-2), and the β2-Adrenergic Receptor Intrinsically Modulates the Level of IgG1 and IgE Produced per B Cell

Abstract: Our findings using B cells from either wild-type, CD86-deficient, or β2-adrenergic receptor (β2AR)-deficient mice suggest three mechanisms by which the level of IgG1 and IgE production can be increased on a per cell basis. Trinitrophenyl-specific B cells enriched from unimmunized mouse spleens were pre-exposed to Ag and/or the β2AR ligand terbutaline for 24 h before being activated by either a β2AR-negative Th2 cell clone or CD40 ligand/Sf9 cells and IL-4 in the presence or absence of an anti-CD86 Ab. Data sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
129
4
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 136 publications
(144 citation statements)
references
References 60 publications
(35 reference statements)
8
129
4
3
Order By: Relevance
“…In addition, full activation of these cells requires the binding of costimulatory molecules expressed on one cell to costimulatory molecules expressed on the other (3,4). One such costimulatory molecule is CD86 (B7-2), which is expressed at a low level on a resting B cell (5,6), but is up-regulated following the stimulation of BCR (7,8), CD40 (9,10), MHC class II (11), LPS receptor (5,7,12,13), IL-4R (14,15), and/or ␤ 2 -adrenergic receptor (␤ 2 AR) (16,17). CD86 binds to the costimulatory molecule CD28 on the Th cell to increase the expression of the costimulatory molecule CD40 ligand (CD40L) on the Th cell and also to increase the level of cytokine produced by the Th cell (13,15,18).…”
Section: Selective Regulation Of Mature Igg1 Transcription By Cd86mentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, full activation of these cells requires the binding of costimulatory molecules expressed on one cell to costimulatory molecules expressed on the other (3,4). One such costimulatory molecule is CD86 (B7-2), which is expressed at a low level on a resting B cell (5,6), but is up-regulated following the stimulation of BCR (7,8), CD40 (9,10), MHC class II (11), LPS receptor (5,7,12,13), IL-4R (14,15), and/or ␤ 2 -adrenergic receptor (␤ 2 AR) (16,17). CD86 binds to the costimulatory molecule CD28 on the Th cell to increase the expression of the costimulatory molecule CD40 ligand (CD40L) on the Th cell and also to increase the level of cytokine produced by the Th cell (13,15,18).…”
Section: Selective Regulation Of Mature Igg1 Transcription By Cd86mentioning
confidence: 99%
“…Although these findings were attributed to a lack of CD28 costimulation on the Th2 cell that resulted in a decrease in the level of IL-4 and CD40L costimulation provided to the B cell, these findings also suggested that CD86 costimulation might generate a signal within the B cell to regulate the level of a Th celldependent Ab response. Recent in vitro data show that the stimulation of CD86 on a B cell activated through CD40 and the IL-4R with or without BCR stimulation increases the level of IgG1 and IgE produced (16,25) and differentially affects the level of antiapoptotic and proapoptotic molecules expressed (26). Likewise, both host and donor B cells from chimeric mice that received donor cells from CD80/CD86-deficient mice and were challenged with a protein Ag were able to produce Ag-specific IgG1, but the level of IgG1 produced by the CD80/CD86-deficient cells was decreased compared with that of the host B cells (27).…”
Section: Selective Regulation Of Mature Igg1 Transcription By Cd86mentioning
confidence: 99%
See 3 more Smart Citations